Highly stable Li1.2Mn0.54Co0.13Ni0.13O2 enabled by novel atomic layer deposited AlPO4 coating. (April 2017) - Xiao, Biwei; Wang, Biqiong; Liu, Jian; Kaliyappan, Karthikeyan; Sun, Qian; Liu, Yulong; Dadheech, Gayatri; Balogh, Michael P.; Yang, Li; Sham, Tsun-Kong; Li, Ruying; Cai, Mei; et al.
Abstract: Lithium-rich layered material is one of the most promising candidates of cathode materials for next-generation electric vehicles. However, one of the major issues that pertains to this material is the oxygen release during initial charge, which results in low initial coulombic efficiency (CE), intense electrolyte oxidation and thermal instability. In this study, we have conducted aluminum phosphate (AlPO4 ) coating via atomic layer deposition (ALD) approach to protect the surface of this cathode material powders. It was found that part of the C2/m Li2 MnO3 phase turned into a spinel-like phase during the ALD process. The oxygen release has been effectively suppressed by such transformation, the initial CE increased from 75.2% for the bare electrode to 86.2% for the electrode with only 5 ALD cycles of AlPO4 coating. Furthermore, AlPO4 was also found to be more effective in improving the thermal stability of the cathode material comparing to bare or Al2 O3 coated samples. Our study has provided a new possible solution towards cathode materials with high thermal resistance via conformal coating. Graphical abstract: Highlights: The application of ALD-derived AlPO4 in the coating of cathode materials is reported for the first time. For the first time, consequences of ALD process on the structure of HENMC has been investigated. The effect of ALD derived AlPO4 coating on the electrochemical performance of HENMC was investigated comprehensively. The thermal stability of the HENMC was examined by comparing the bare sample, Al2 O3 coated sample and AlPO4 coated sample.